Analisis Potensi Penyebab Rumah Tangga Miskin Jawa Tengah - sri Ningsih (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2018)
This study aims to analyze the potential causes of poor households in Central Java. Analysis using logistic regression. The study used secondary data from the National Socio-Economic Survey (Susenas) in Central Java 2018 collected by Badan Pusat Statistik. The study concluded that there are 6 (six) main characteristics: the area of residence, gender, education level, number of household members and the status of working head of household, which has the potential to cause household poverty in Central Java. Households living in rural areas have the opportunity to be poor at 1,398 times higher than in urban areas. On that basis, it is recommended to improve the economy of rural areas.